Leadership of the Keuchik in Improving the Performance of the Apparatus of Lamgeu Baro Village, Sukamakmur District, Aceh Besar Regency - Nurliana, Nurliana; Safitri, Ema; Ellyana, Cut Putri (Dinasti International Journal of Management Science, 2023)
Leadership is the process of influencing others so that the person voluntarily wants to carry out joint activities to achieve predetermined goals, success or failure in the implementation of community services, is influenced by leadership, conversely, weakness in leadership is one of the causes of performance collapse. The formulation of the problem of this research is First, How is Leadership Direction and Control in Improving the Performance of the Lamgeu Baro Village Apparatus, Sukamakmur District, Aceh Besar Regency. Second, How is the Implementation and Supervision of the Performance of the Lamgeu Baro Village Apparatus, Sukamakmur District, Aceh Besar Regency. The method used in this study is qualitative. The informants in this study were the Village Head, Secretary, Head of Government Section, Village Head Office Staff, and the community. In this study, data collection techniques used observation, interviews, and documentation. Websites that can be accessed via the internet, books, and journals of other written works. The results of the research that has been carried out indicate that evaluation can be carried out based on whether the policy has succeeded in achieving its objectives, as well as its impact on society and the environment. Individual understanding and awareness of work regulations and the importance of obeying them. This awareness can be increased through socialization, training, and clear communication about work regulations. Good timely implementation and the availability of adequate facilities, the village can provide better public services to the community, accelerate development, and improve the quality of life in the village. Conclusion Through the implementation that has been conveyed, it is hoped that the Keuchik leadership can become a pillar in achieving superior village apparatus performance, meeting community needs, and realizing a more advanced village.